PENGEMBANGAN E-LEARNING BERBASIS WEBSITE MENGGUNAKAN MODEL AGILE PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SMA AS SAKINAH PAKENJENG - Arpit; Siti Husnul Bariah; Dian Rahadian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information and communication technology has encouraged the integration of digital learning media to improve the effectiveness of the teaching and learning process. However, the learning process at SMA Assakinah Pakenjeng is still conducted conventionally, resulting in limited utilization of digital technology for delivering learning materials, assignments, and assessments. This study aims to develop a website-based e-learning system using the Agile model for the Information and Communication Technology (ICT) subject at SMA Assakinah Pakenjeng, to determine the results of functional testing using the Black Box Testing method, and to analyze students' responses to the developed system. This research employed the Agile development model, which consisted of several sprints involving requirements analysis, system design, implementation, testing, and evaluation. Functional testing was conducted using the Black Box Testing method, while student responses were collected through a response questionnaire. The results indicate that the website-based e-learning system was successfully developed according to user requirements. The Black Box Testing results showed that all main system functions operated as expected. Furthermore, the student response questionnaire achieved a score of 88.82%, which falls into the very good category, indicating that the system is easy to use, supports the learning process effectively, and provides a more flexible learning experience. Therefore, the developed website-based e-learning system is considered suitable for supporting the teaching and learning process in the Information and Communication Technology subject at SMA Assakinah Pakenjeng.